2001
DOI: 10.1007/s00464-001-8154-2
|View full text |Cite
|
Sign up to set email alerts
|

Are the favorable outcomes of splenectomy predictable inpatients with idiopathic thrombocytopenic purpura (ITP)?

Abstract: These results suggest that the response to splenectomy (laparoscopic and open) in patients with ITP cannot be adequately predicted on the basis of presplenectomy clinical variables. However, disease duration and patient age should be taken into consideration when selecting patients for splenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
2
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 14 publications
4
22
2
5
Order By: Relevance
“…It can be concluded that a more successful disease outcome following splenectomy can be predicted for younger patients. Tsereteli et al write that the duration of the disease prior to the operation is also one of the predictive factors, which should be considered for successful ITP outcome following splenectomy (22). In our study the mean value of the duration of the disease prior the operation (45 ± 54.4 months) did not influence the disease outcome following the operation in a statistically significant way (ANOVA; F = 0.297; p = 0.750).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…It can be concluded that a more successful disease outcome following splenectomy can be predicted for younger patients. Tsereteli et al write that the duration of the disease prior to the operation is also one of the predictive factors, which should be considered for successful ITP outcome following splenectomy (22). In our study the mean value of the duration of the disease prior the operation (45 ± 54.4 months) did not influence the disease outcome following the operation in a statistically significant way (ANOVA; F = 0.297; p = 0.750).…”
Section: Discussioncontrasting
confidence: 50%
“…The side -effects of GC therapy and the development of minimally invasive surgical techniques facilitated the introduction of laparoscopic splenectomy in the treatment of ITP. 50 -80 % of the patients are treated with splenectomy, and achieve full remission following the operation in 49 -93 % of the cases, therefore various perioperative predictive factors are searched that would allow predicting ITP outcome after the operation (3,9,14,22,23). If 30 days after the operation and longer PLT count is > 150 x 10 9 /L (more recent publications > 100 x 10 9 /L), without additional therapy, except cases, when GC dose is gradually cancelled after the operation, the remission is considered to be complete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The good longterm results obtained after LS for ITP have revived interest in ITP as surgical disease. Several studies have attempted to investigate the predictive factors for success after LS [11,28]. Lower response has been reported in patients older than 40 years of age with long-term corticoid treatment or a post-splenectomy platelet count lower than 100 · 10 9 /L, and these variables have been considered as predictive factors of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…But the overall complication rate is low in LS. [24,30] As our study, Tsereteli et al, [31] did not find any significant difference between the open and laparoscopic procedures as a predictive factor of favorable outcome.…”
Section: Discussionmentioning
confidence: 50%